Az európai kormányzás új lehetősége - az Európai Területi Együttműködés jogi keretei az új európai kohéziós politikában (New Opportunity of the European Governance – The Legal Framework of the European Territorial Coperation in the New Cohesion Policy) - Zsuzsanna Fejes (DETUROPE)
The lack of unified legal regulation of the cross-border cooperation originates from the diversity of the legal systems was absent from the legislation of the European Union for a long time. The aim of the study is to examine the Regulation (EC) No 1082/2006 on EGTC, which is a response to the lack of legal and institutional instruments, and ensures common cooperation facilities with legal personality for the local and regional authorities and member states. The study summarizes the advantages of EGTC, how to response a new alternative to increase the efficiency, legitimacy and transparency of the activities of territorial cooperation, and at the same time secures legal certainty. The revised EGTC Regulation (1302/2013/EU) contains the most important pieces of legislation related to the cohesion policy and most of the programmes funded by the EU in the period 2014-2020.